The moderated mediating role of social support and locus of hope on the relationship between self-efficacy and self-regulation among illicit substance use patients within therapeutic communities - Embalsado, Justin Vianey M. (Animo Repository, 2018)
The therapeutic communities emphasize the development of the patient’s motivation and self- efficacy towards recovery. The patient’s abstinence self-efficacy is identified in the study as an important predictor of temptation restraint with the locus of hope as possible mediators and, peer, staff, and treatment support as moderators. One hundred forty-four patients that have spent three to six months in the therapeutic communities participated in the study. Abstinence self-efficacy served as the predictor with temptation restraint as the outcome while the internal and external locus of hope served as parallel mediators. Peer, staff, and treatment support respectively served as moderators within the mediation model. The results indicate that peer support is a significant moderator that serves as an important protective factor between the patient’s abstinence self- efficacy and internal locus of hope. Meanwhile, the results failed to support the hypothesized mediation of the loci of hope, and the moderation of staff and treatment support. Implications of the study indicate the need for a non-directive approach, strength-based programs, and peer- facilitated activities.